2013
DOI: 10.1017/s0954579413000217
|View full text |Cite
|
Sign up to set email alerts
|

Language and internalizing and externalizing behavioral adjustment: Developmental pathways from childhood to adolescence

Abstract: Two independent prospective longitudinal studies that cumulatively spanned the age interval from 4 years to 14 years used multi-wave designs to investigate developmental associations between language and behavioral adjustment (internalizing and externalizing behavior problems). Altogether 224 children, their mothers, and teachers provided data. Series of nested path analysis models were used to determine the most parsimonious and plausible paths among the three constructs over and above stability in each acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
153
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 99 publications
13
153
3
4
Order By: Relevance
“…Taken together the work of Bornstein and colleagues and the results of the current study, suggest comorbidity between language and behavioural problems. As proposed by Bornstein et al (2013), it is possible that poor behavioural adjustment may limit language development, which is consistent with the present study. For example, in social or academic situations internalising symptoms (such as anxiety and depression) may undermine the use of children's language which in turn may limit their use of language both academically and in social situations (Bornstein et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Taken together the work of Bornstein and colleagues and the results of the current study, suggest comorbidity between language and behavioural problems. As proposed by Bornstein et al (2013), it is possible that poor behavioural adjustment may limit language development, which is consistent with the present study. For example, in social or academic situations internalising symptoms (such as anxiety and depression) may undermine the use of children's language which in turn may limit their use of language both academically and in social situations (Bornstein et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…As proposed by Bornstein et al (2013), it is possible that poor behavioural adjustment may limit language development, which is consistent with the present study. For example, in social or academic situations internalising symptoms (such as anxiety and depression) may undermine the use of children's language which in turn may limit their use of language both academically and in social situations (Bornstein et al, 2013). However given the constraints of the present study further research using longitudinal studies is needed to further investigate this hypothesis and to disentangle the direction of the association between language and behavioural problems.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Instead there is a strong body of evidence showing that it is language deficiencies (including delays in receptive vocabulary) which result in behavioural adjustment problems in children and adolescents across both internalising and externalising domains (Bornstein, Hahn, & Joan, 2013;Petersen et al, 2013;Yew & O'Kearney, 2013). However, contrary to the results of the current study, some of this previous work has shown that this relationship did not hold in reverse.…”
Section: Discussioncontrasting
confidence: 87%